(untitled) (Medico Legal Update, 2020)
Background: Air pollution is associated with cardiovascular morbidity and mortality. An oxidative stress arising from particulate matter has been shown to activate a number of redox responsive signaling pathways in target cells. This pathway is involved in gene expression that plays a role in the response to inflammation and pathological changes including the expression of mitogen-activated protein kinase (MAPK). Objective: To describe the effect of soot particulate exposure towards MAPK expression in the mechanism of cardiovascular disruption. Design: This research was an experimental research by using “post test only control group design” approach. Subjects: The experiment was conducted in laboratory female rats (Rattus novergicus) and consisted of 3 groups: Methods: Control group -exposed by soot particulate with the concentration of 532 mg/m3 an hour each day for 30 days, without soot particulate exposure- (n=10); Treatment 1 group (n=2); Treatment 2 group -exposed by soot particulate with the concentration of 1064 mg/m3 an hour each day for 30 days- (n=12). Results: The soot particulate significantly induced an increase in MAPK expression in the treatment 1 group (the number of immunoreactive cells: 51 (31-216) vs 2 (0-50), p=0.001; immunoreactive score (IRS) index: 2 (1-4) vs 1 (0-2), p=0.048) and in treatment 2 group (the number of immunoreactive cells: 73 (17-203) vs 2 (0-50), p=0.000; IRS: 2 (1-4) vs 1 (0-2), p=0.01) compared to control group. There was a significant increase in MAPK expression which was measured from the total number of immunoreactive cells in Treatment 1 (p=0.001) and Treatment 2 group (p=0.000) compared to Control group. Conclusion: The Exposure to soot particulates significantly increased MAPK expression in experimental rats.